Meningkatkan Minat dan Hasil Belajar Fisika Melalui Media Pembelajaran Physics Courseware - Mubarus Naibaho (SAP (Susunan Artikel Pendidikan), 2021)
Electric current is defined as the flow direction of positive charge from the positive pole to the negative pole that is understood in imaginary. Numbers of formulas and facts give complicated and boring impression. Preparation, implementation, and completion of practice require a lot of energy and time, so the use of equipment in the laboratory is also one of the causes for the weak understanding of grade IX / 2 students at SMP Negeri 85 Jakarta. Ms. Power Point, as a presentation medium, also provides various facilities for creating, processing, inputting audio files, video files, and even animation.  This program was developed as a physics teaching tool (Physics Courseware) to increase students' understanding and interest in physics lessons. The difficulty in understanding the material with the existence in learning media was then carried out in an action which was implemented in the odd semester of the 2016/2017 academic year with 2 cycles. Actions in cycle I and cycle II were through the use of Media Physic Courseware and it was seen that there was a change in interest and learning outcomes. The research success indicator was seen from the performance indicator, that was if all the observed aspects had reached 85% or more. After all actions taken, and from the result of observation, assessment, and discussion, it was concluded that the use of physics courseware can increase student interest and learning outcomes.